Graduación en el Teatro Popular Melico Salazar, julio, 2011. (UNED, 2011)
Registro de ingreso. Aparecen Violeta Díaz,Tatiana Bermúdez, Dora García, Ericka Campos, Yuri Quesada, Leonardo Guillén, Carolina Sánchez